Addressing socio-ecological development challenges in the digital age: Exploring the potential of Environmental Virtual Observatories for Connective Action (EVOCA). (1st November 2018) - Cieslik, K.J.; Leeuwis, C.; Dewulf, A.R.P.J.; Lie, R.; Werners, S.E.; van Wessel, M.; Feindt, P.; Struik, P.C.
Abstract: Climate change, (a) biotic stresses and environmental degradation are adversely affecting the sustenance of farming communities in Africa. Addressing such challenges requires effective collective action and coordination among stakeholders, which often prove difficult to achieve. Timely and context-specific information on relevant environmental dynamics holds considerable promise to overcome these problems. This paper investigates the role of citizen science in facilitating knowledge co-creation and sharing between academia, development actors and users in developing country contexts. In our approach, we focus on information sharing platforms (known as Environmental Virtual Observatories, EVOs) and their potential to facilitate adaptive decision-making in six rural case-study areas in Africa. We complement the existing theory on EVOs with a focused exploration of the connective function of ICT-enabled multi-stakeholder exchange. We propose that increased connectivity may enable new forms of collective action (labelled 'connective action'), relevant to addressing socio-ecological challenges. Along these lines, this paper presents the theoretical and conceptual grounding of a research program that aspires to develop Environmental Virtual Observatories for Connective Action (EVOCAs) and to explore their potential for improved crop, water, livestock and disease management in rural Africa.